Addition of pig manure hydrolysate as a carbon source to enhance nitrate removal from piggery wastewater under different HRTs. Issue 3 (June 2019) - Yang, Jie; Wang, Dehan; Luo, Zifeng
Graphical abstract: Highlights: Pig manure carbon source (PMC) was obtained easily (70 °C, 1 h). Pig manure hydrolysate as a carbon source for the first time. PMC performed better than the sodium acetate. PMC improved the denitrification rate, effectively. With the PMC, NO3 -N removal rate was 99%, TN removal rate was 90%. Abstract: To develop a quick, efficient, economical and easy method of obtaining a carbon source for piggery wastewater, thermo-alkaline treatment of pig manure hydrolysate as an external carbon source (PMC), which contains a high concentration of VFAs, was used. Batch experiments were carried out to determine the effect of the COD/TN ratio on piggery wastewater denitrification using PMC, and a comparison was made between PMC and sodium acetate for the denitrification at the optimum COD/TN ratio. Then, the effect of PMC on piggery wastewater denitrification was proven in a sequencing batch reactor. The results show that when PMC is applied, the appropriate C/N ratio for denitrification is 6.5, which is equivalent to an addition of 3.8%. Under these conditions, PMC performed better than sodium acetate. With PMC, the contents of NO2 -N and NO3 -N in the SBR under three different HRTs were less than 0.02 mg/L and 5 mg/L, respectively, and the TN removal rate was 90%. The highest denitrification rate of SBR was 25.37 mg NO3 -N/(g VSS h).